An assessment of diet overlap of two mesocarnivores in the North West Province, South Africa - van der Merwe, I.; Tambling, C.; Thorn, M.; Scott, D.; Yarnell, R.; Green, M.; Cameron, E.; Bateman, Bill (Universiteit Stellenbosch * Department of Botany and Zoology, 2009)
We used scat analysis to study the diet of twosympatric medium-sized carnivores: brown hyaenaand black-backed jackal, in the NorthWest Province ofSouth Africa. Seven major dietary categories wereidentified from the scats, with mammal remains beingmost common for both species. Brown hyaena scatscontained more large mammal remains, which togetherwith the presence of invertebrates (in 50% of allbrown hyaena scats), suggests that they mainly scavenged.Jackal scats contained a higher proportionof small mammal remains, suggesting that jackalsactively hunted more often than brown hyaenas did.The diets differed significantly between the twospecies, even though diet overlap was fairly high(0.79). Further analysis, albeit based on small samplesizes, suggests that diet of these mesopredators differbetween protected reserves with apex predatorsand unprotected areas without apex predators, thusconfounding generalizations. Further studies aretherefore required to investigate possible mesopredatorrelease when apex predators are absent.Key words: apex predators, carnivore diets, scatanalysis, brown hyaena, black-backed jackal.